Naturalization of European plants on other continents: The role of donor habitats - Kalusová, Veronika (Proc Natl Acad Sci U S A, 2017)
The success of European plant species as aliens worldwide is thought to reflect their association with human-disturbed environments. However, an explicit test including all human-made, seminatural and natural habitat types of Europe, and their contributions as donor habitats of naturalized species to the rest of the globe, has been missing. Here we combine two databases, the European Vegetation Checklist and the Global Naturalized Alien Flora, to assess how human influence in European habitats affects the probability of naturalization of their plant species on other continents. A total of 9,875 native European vascular plant species were assigned to 39 European habitat types; of these, 2,550 species have become naturalized somewhere in the world. Species that occur in both human-made habitats and seminatural or natural habitats in Europe have the highest probability of naturalization (64.7% and 64.5% of them have naturalized). Species associated only with human-made or seminatural habitats still have a significantly higher probability of becoming naturalized (41.7% and 28.6%, respectively) than species confined to natural habitats (19.4%). Species associated with arable land and human settlements were recorded as naturalized in the largest number of regions worldwide. Our findings highlight that plant species’ association with native-range habitats disturbed by human activities, combined with broad habitat range, play an important role in shaping global patterns of plant invasions.